Accounting for Different Uncertainties: Implications for Climate Investments? - Svenja Hector (Fondazione Eni Enrico Mattei (FEEM), 2013)
The paper clarifies the link between changes in risk aversion and the effect on the consumption discount rate. In a general framework that can cope with various forms of uncertainty, it is shown that the response of the consumption discount rate to a change in risk aversion depends on some fundamental properties of the considered uncertainties. The application of this general result to specific forms of uncertainty extends existing results to more general forms of risk and yields a new result on preference uncertainty.
Keywords: H43; D81; Q54; 330; Discount Rate; Risk Aversion; Kreps-Porteus-Selden; Risk-Sensitive Preferences; Uncertain Preferences; Climate Change